Ø¯Ø§ÙØ¹ÙŠØ© ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ ØªÙ„Ø§Ù…ÙŠØ° Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ø³ÙˆÙ…Ù†Ø¨ ÙˆØ§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© Ù†ÙˆØ± Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø¨Ø³ÙˆÙ…Ù†Ø¨ - Qibtiyah, Lutfatul; Alfinnas, Shulhan (AT-TA'LIM, 2019)
Motivation plays important role in language learning. It has contributed to grow student’s interest in learning Arabic language. This research is aimed to describe real case in State Islamic Senior High School (MAN) Sumenep and Nurul Islam Senior School Sumenep. This study was conducted through qualitative research approach which multi-case study was as research design. The findings are; a. the intrinsic motivation to learn Arabic are that students have an interest in Arabic owing to they need to understand the Quran and intend to continue to pursue higher level, and have positive attitude towards Arabic, b. the extrinsic motivations are their father boost and encourage them to learn the Arabic language, and majority of their teacher are able to use the Arabic language well, and then the Arabic teacher chooses the precise and good method of teaching and learning which enable them to enjoy deepening that language, as well as the heads of both schools have good ability in applying the Arabic language. Furthermore, by various methods of teaching and learning, the Arabic teacher can engage the student motivation to learn that language which formally is used as official language of Islam. In additionally, the use of many kinds teaching medias and instruments and also advice and assistance helps the educator to increase pupil spirit in understanding and using the language.